2017
DOI: 10.1016/j.stem.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

PRC2 Facilitates the Regulatory Topology Required for Poised Enhancer Function during Pluripotent Stem Cell Differentiation

Abstract: Highlights d Poised enhancers are necessary for the induction of major anterior neural genes d Poised enhancers physically contact their target genes in embryonic stem cells d The interaction between poised enhancers and their target genes is PRC2 dependent d PRC2 provides major anterior neural loci with a permissive regulatory topology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
270
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(286 citation statements)
references
References 82 publications
(106 reference statements)
16
270
0
Order By: Relevance
“…Thereby, PcG dependent interactions may form 3D chromatin hubs that coordinate repression and the activation of early (neuro-) developmental regulators ( Figure 3). Beyond preventing precocious activation of early neural genes, PcG proteins can also preset future activation of major anterior neural genes once the differentiation signal has been received [12]. In this scenario, PcG proteins endow poised enhancers with a permissive regulatory topology that enables pluripotent cells to respond effectively to neural induction signals (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereby, PcG dependent interactions may form 3D chromatin hubs that coordinate repression and the activation of early (neuro-) developmental regulators ( Figure 3). Beyond preventing precocious activation of early neural genes, PcG proteins can also preset future activation of major anterior neural genes once the differentiation signal has been received [12]. In this scenario, PcG proteins endow poised enhancers with a permissive regulatory topology that enables pluripotent cells to respond effectively to neural induction signals (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…domains form and resolve dynamically during successive neurodevelopmental stages to regulate diverse sets of target genes. Moving beyond the linear chromatin landscape, most recently Cruz-Molina et al [12] showed that PRC2 mediated contacts with poised enhancers (see Section 4.1) and promoters in ESCs established a permissive environment that preconditioned the induction of major anterior neural genes (e.g., Lhx5, Six3, Sox1, Wnt8b, Sox21) in NPCs. Genome-wide mapping of EP300 and H3K27me3 detected ≈1000 poised enhancers that were enriched in genes that were necessary for the development of the anterior neural tube.…”
Section: Polycomb Group Complexes In Neural Progenitor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold Spring Harbor Laboratory Press on May 9, 2018 -Published by genome.cshlp.org Downloaded from Collectively, studies in different systems across multiple species using 3C-based methods and derivatives identified two types of enhancer-promoter interactions: loops formed de novo and pre-existing loops (Melo et al 2013;Eijkelenboom et al 2014;Freire-Pritchett et al 2017;Montavon et al 2011;Ghavi-Helm et al 2014;Apostolou et al 2013;Cruz-Molina et al 2017). While de novo (also called instructive) interactions appear concomitant with changes in the target gene activity, pre-existing (also called permissive) interactions are formed prior to gene activation and are thought to facilitate timely transcriptional induction (de Laat and Duboule 2013;Bouwman and de Laat 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, both activation by enhancers and repression by the PcG proteins are known to involve higher-order interactions that place distant regions adjacent to one another by either looping or forming discrete domains of interaction (Deng et al 2012;Williamson et al 2012;Kundu et al 2017). There have been suggestions that PcG-mediated looping might help with driving activating interactions (Cruz-Molina et al 2017). Another area of mechanistic overlap involves the necessity of altering chromatin structure to facilitate binding by the full complement of factors that are needed to generate a PRE or an enhancer.…”
mentioning
confidence: 99%